2009
DOI: 10.1007/s00224-009-9173-y
|View full text |Cite
|
Sign up to set email alerts
|

Between Order and Chaos: The Quest for Meaningful Information

Abstract: The notion of meaningful information seems to be associated with the sweet spot between order and chaos. This form of meaningfulness of information, which is primarily what science is interested in, is not captured by both Shannon information and Kolmogorov complexity. In this paper I develop a theoretical framework that can be seen as a first approximation to a study of meaningful information. In this context I introduce the notion of facticity of a data set. I discuss the relation between thermodynamics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Shannon defined information as a reduction of uncertainty [149]. Adriaans addresses the idea of meaningful information [4]. Buckland defined information-as-thing, information-asknowledge and information-as-process [26].…”
Section: Discussionmentioning
confidence: 99%
“…Shannon defined information as a reduction of uncertainty [149]. Adriaans addresses the idea of meaningful information [4]. Buckland defined information-as-thing, information-asknowledge and information-as-process [26].…”
Section: Discussionmentioning
confidence: 99%
“…Since Kolmogorov complexity is non-computable we have to rely on approximations to apply this theory in practical situations, but work of Cilibrasi and Vitányi (2006;Vitányi et al 2008) and Adriaans (2009) has shown that using industrial data compression programs is a viable option for a rich class of problems. The mutual information between two objects for instance can be approximated with industrial compression algorithms using the so-called normalized compression distance (NCD): NCD x; y ð Þ ¼ C xy ð Þ À min CðxÞ; CðyÞ ð Þ max CðxÞ; CðyÞ ð Þ Here C(xy) indicates the complexity of the concatenation of x and y.…”
Section: A Short Theoretical Digressionmentioning
confidence: 99%
“…It is quite surprising that this notion of facticity that is closely related to Sartre's notion of the absurd, and is supposed to belong to the more obscure phenomena in Heidegger's philosophy, emerges in the context of a philosophy of information (Heidegger 1977;Gadamer 1975). It is possible to develop a theory of informational esthetics (Adriaans 2009) on the basis of this formal notion of facticity (with the central insight that good artists optimize facticity).…”
Section: The Problem Of Semantic Informationmentioning
confidence: 99%
See 2 more Smart Citations